PENATAAN AGROWISATA JALUR TRACKING SURADADI DI DESA BELIMBING KECAMATAN PUPUAN TABANAN - N.N. Soniari; N.W. Siti; N.W. Suniti; I.M. Adhika (Buletin Udayana Mengabdi, 2023)
The purpose of this partner village development program is to develop the potential of the village as optimally as possible and empower the target community. One aspect that has the potential to be developed in Belimbing village is agro-tourism. Nature tourism requires supporting facilities such as trajectories/paths for tourists to certain tourist locations. The Suradadi Tracking track was deliberately created and arranged for the benefit of local residents as a production road and for tourists who want to enjoy the beauty of the natural panorama such as rice terraces and stunning mountain views. Belimbing Village has natural tourism potential and community traditions that have not been managed optimally. Since its stipulation as a National Priority Development Area (KPPN), this village has begun to improve, reviving the existing potential with the support of the local government and collaborating with various parties. The Partner Village Development Program Team (PPDM) from Udayana University is one of the parties that collaborates with Belimbing village. One of the activities of this second year program is the arrangement of the Suradadi tracking agrotourism route as part of the saptapesona element. Collaboration between partners, KKN students, local residents, village heads and the Unud PPDM team carried out mutual cooperation to realize the Suradadi tracking path. Along the route, planting of ornamental plants "Puring and fruit" was carried out, as well as socialization of local waste processing technology (TOSS) and preparing special trash bins for inorganic waste so that it added the clean, cool and beautiful elements of Saptapesona. Marketing of village tourism packages is done through the “Godevi” (Go Destination Village) application which involves Pokdarwis and the Godevi team. Keywords : PPDM, Belimbing Village, agro-tourism, tracking path, Sapta Pesona